The Role of Intestinal Translocation in the Pathogenesis of Pneumonia in Acute Poisoning and the Contribution of Intestinal Lavage to Its Prevention and Resolution - V. A. Matkevich; T. T. Tkeshelashvili; A. G. Vorobyova; N. E. Stolbova; M. M. Potskhveriya; Yu. S. Goldfarb (Неотложная медицинская помощь)
RELEVANCE. Among the deadly complications of severe poisoning, pneumonia occupies a leading position, and therefore the search for new solutions aimed at prevention and treatment of this complication is relevant.   AIM OF THE STUDY. To study the role of intestinal translocation in the pathogenesis of pneumonia in acute poisoning and to evaluate the contribution of intestinal lavage to its prevention and resolution.   MATERIAL AND METHODS. Here at the N.V. Sklifosovsky Research Institute for Emergency Medicine, we analyzed the outcomes of treatment of 1124 patients with severe oral poisoning: by psycho-pharmacological drugs (PPD) — 172 and corrosive substances (CS) — 325 people; with intravenous administration of methadone (M) — 575, as well as 50 patients with alcoholic delirium (AlD) as a complication of PPD and CS poisoning. In cases of PPD and M poisoning, the patients’ Glasgow Coma Scale (GCS) scores ranged from 3 to 5, with respiratory disorders requiring mechanical ventilation. The severity of CS poisoning was due to the 2nd-3rd degree chemical burn of the mucous membrane of the mouth, pharynx, esophagus and stomach. The condition of patients with AlD was severe and corresponded to 29.0 (27.0; 30.0) points on the DELIRIUM RATING SCALE – R – 98. In cases of PPD and CS poisoning, the state of the intestinal microbiocenosis, the permeability of the intestinal barrier, the endotoxin content of gram-negative bacteria in the blood and integral indicators of intoxication were studied. Intestinal lavage (IL) was used in the observed groups (655). Patients in the comparison groups (469) received standard therapy.   RESULTS. Initially detected: intestinal dysbiosis of II–III degree, increased permeability of the intestinal barrier — 3.8–4.9 times higher than normal, a tenfold increase in the content of endotoxin in the blood and a 6-fold increase in the leukocyte index of intoxication. It was established that intestinal lavage effectively cleanses the entire gastrointestinal tract, eliminates intestinal dysbiosis, reduces excessive permeability of the intestinal wall, and is accompanied by a 2-fold decrease in the endotoxin content in the blood and the leukocyte index of intoxication. As a result, pneumonia was registered in cases of PPD poisoning 2.1; M —1.9; CS — 2.4, and AlD — 9.8 times less often than in the comparison groups. Mortality among the patients with PPD poisoning decreased by 7 times, and with M and CS poisoning, as well as with AlD, there were no deaths, while in the respective comparison groups, the mortality rate for pneumonia was 5.1, 7.4, and 17.4 %, respectively. The differences were statistically significant.   CONCLUSION. A pattern in the form of intestinal dysbiosis, excessive permeability of the intestinal barrier, and increased levels of endotoxin in the blood may indicate that the source of the infectious-inflammatory process in the lungs during acute poisoning is the intestine; and the cause-and-effect relationship between the sanitation of the gastrointestinal tract by intestinal lavage and a reduction in the incidence of pneumonia and mortality confirms this hypothesis.